2015
DOI: 10.1002/jbm.b.33551
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of keratin in adhesion, proliferation, adipogenic, and osteogenic differentiation of porcine adipose‐derived stem cells

Abstract: Recently, keratin attracts tremendous interest because of its intrinsic ability to interact with different cells. It has the potential to serve as a controllable extracellular matrix protein that can be used to demonstrate cell mechanism and cell-matrix interaction. However, there have been relatively few studies on the effects of keratin on stem cells. In the present work, we study the effects of human keratin on porcine adipose-derived stem cells (pASCs) and a series of selective cell lines: 3T3 fibroblasts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 56 publications
(116 reference statements)
1
16
0
Order By: Relevance
“…Overall, the results of real-time PCR corroborated the adipogenic and osteogenic differentiation potential of hASCs in keratin scaffolds. The results were consistent with our previous study, showing increasing PPAR-γ and RUNX2 gene expression activities on keratin coating (Wu et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, the results of real-time PCR corroborated the adipogenic and osteogenic differentiation potential of hASCs in keratin scaffolds. The results were consistent with our previous study, showing increasing PPAR-γ and RUNX2 gene expression activities on keratin coating (Wu et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Keratin was prepared from human hair according to the method reported previously (Nakamura, Arimoto, Takeuchi, & Fujii, 2002;Wu, Lin, Cheng, Yang, & Yu, 2017). First, human hair was washed with distilled water three times and then soaked in 300 ml mixture of methanol/chloroform (2:1, v/v; ECHO Chemical Co., Taiwan) for 18-24 hr to remove lipid covering the external part of the hair.…”
Section: Extraction and Identification Of Human Hair Keratinsmentioning
confidence: 99%
“…Five candidate genes were identified by both the transcriptomic and proteomic analyses, and two of these (KRT2 and KRT4) were shown to have similar expression patterns by k-means clustering. As KRT homologs are closely related to hair growth [43][44][45], we separately overexpressed KRT2 and KRT4 in SHF-DPCs and found that KRT4 increased the growth of SHF-DPCs. In addition, our investigation of proliferation-related signaling pathways showed that the ERK signaling pathway was significantly enhanced in Tβ4+ goats, which is consistent with previous reports that this signaling pathway is involved in the regulation of hair follicle development in a variety of model animals [41,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Keratins have outstanding cytocompatibility due to their cell adhesive Arg–Gly–Asp (RGD) and Leu–Asp–Val (LDV) sequences . Recently, Yu group demonstrated that keratins could improve adhesion, proliferation, and viability of porcine adipose‐derived stem cells . Metal ions (e.g., Ag + and Au 3+ ) can be easily bound under the chelating effect and electrostatic attraction by virtue of the abundant free amino and carboxyl groups of keratins .…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, Yu group demonstrated that keratins could improve adhesion, proliferation, and viability of porcine adipose-derived stem cells. 9 Metal ions (e.g., Ag + and Au 3+ ) can be easily bound under the chelating effect and electrostatic attraction by virtue of the abundant free amino and carboxyl groups of keratins. [10][11][12] In addition, the formed metal nanoparticles are stable due to the chemical gold-sulfur (Au-S) or silversulfur (Ag-S) bonds.…”
Section: Introductionmentioning
confidence: 99%